Effectiveness of Oil Palm Farmers’ Adaptation Strategies In Facing Social Change - Elfisa Natalia Br Pandia; Apri Andani; Lathifah Khairani; Anggita Tresliyana Suryana (AGRITEPA: Jurnal Ilmu dan Teknologi Pertanian, 2026)
Purpose: This study aims to analyze the extent of social change, adaptation strategies, and the effectiveness of adaptation strategies among oil palm farmers, as well as to examine the influence of social change on adaptation strategies and its impact on the effectiveness of farmers’ adaptation strategies in Pondok Kelapa Subdistrict, Central Bengkulu Regency. Methodology : This study uses a quantitative approach with a survey method on oil palm farmers as research respondents. Data were collected through questionnaires and analyzed using the Structural Equation Modeling Partial Least Square (SEM-PLS) method to test the influence between social change, adaptation strategies, and the effectiveness of adaptation strategies. Results: The results of the study indicate that social change has a significant impact on the adaptation strategies of oil palm farmers. The adaptation strategies employed by farmers were also found to have a significant impact on the effectiveness of these strategies, whereas the direct impact of social change on the effectiveness of adaptation strategies was not significant. Findings: This finding indicates that the higher the adaptation strategies implemented by farmers, the higher the effectiveness of adaptation strategies achieved in maintaining the sustainability of oil palm farming amid the dynamics of social change. Novelty: The novelty of this study lies in its examination of the role of adaptation strategies as a mediating variable in the relationship between social change and the effectiveness of adaptation strategies among oil palm farmers, using the SEM-PLS approach. Originality: The originality of this study lies in its research subjects and location palm oil farmers in Pondok Kelapa Subdistrict, Central Bengkulu Regency as well as in its focus on the effectiveness of farmers’ adaptation strategies in coping with social change. Conclusion : Farmers’ ability to respond to social changes through appropriate adaptation strategies is a key factor in enhancing the effectiveness of adaptation and the sustainability of oil palm farming. Type of Paper : Research article.